PERBAIKAN KINERJA PENANGANAN KARGO IKAN TUNA; Di TERMINAL KARGO BANDAR UDARA INTERNASIONAL SOEKARNO HATTA - Dony Rahmad Pranoto; Marimin Marimin; Yandra Akreman (Jurnal Manajemen & Agribisnis, 2016)
The objectives of this study were 1) to identify the tuna cargo handling conducted in the export warehouse of PT. XYZ, 2) to determine the main variables that affect the performance of tuna cargo handling in the export warehouse of PT. XYZ, and 3) to determine what policies can be used to improve the performance of tuna cargo handling in the export warehouse of PT. XYZ. This research was conducted by using the descriptive methodology i.e. a discrete simulation model of the process of tuna cargo handling in the export warehouse of PT. XYZ by utilizing ARENA software. In the policy making of tuna cargo handling improvements, the Analytical Network Process, Benefit, Opportunity, Cost, and Risk (ANP BOCR) were also used. The simulation results point out that the existing conditions contribute to the delay level of tuna cargo delivery by 12% with the quality level of 22,934%. Delays in tuna cargo delivery have led to an increase in operational costs by 1,5%. ANP BOCR results highlight that opening a special lane for perishable cargo handling will improve the performance of tuna cargo handling in the export warehouse of PT. XYZ. Furthermore, the results of discrete model simulations on the improvement scenario of tuna cargo handling performance show that by opening a special lane for perishable cargo handling, it can ensure delivery schedule to be accurate indicated by the level of on time delivery reaching up to 100%, with an average quality rate of 86.013%. By speeding up the processing period (with an average of 81.519 minutes), the delay of cargo delivery up to 100% will be reduced; therefore, the quality of tuna is maintained in a good condition with the histamine level of 6,7 ppm.Keywords: ANP BOCR, tuna, ARENA simulation system model, air cargo performance, perishable cargo